2008
DOI: 10.1016/j.juro.2008.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Fournier's Gangrene Severity Index in a Large Contemporary Series

Abstract: The Fournier's gangrene severity index remains an objective and simple method to quantify the extent of metabolic aberration at presentation in patients with Fournier's gangrene. A Fournier's gangrene severity index threshold value of 9 is sensitive and specific for predicting mortality in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
122
5
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(170 citation statements)
references
References 18 publications
25
122
5
18
Order By: Relevance
“…On the contrary, some other studies have not shown any difference between survivors and non-survivors as for the time to admission. [7,11] Furthermore, in their studies McCormack et al [19] determined that the time be- Logically, an increased body percent involved would cause sepsis and result in an increased risk for mortality, however two studies proposed that the extent of the disease was not predictive of outcome. [2,4] Three separate studies found significantly higher incidence of the disease in body in the non-survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, some other studies have not shown any difference between survivors and non-survivors as for the time to admission. [7,11] Furthermore, in their studies McCormack et al [19] determined that the time be- Logically, an increased body percent involved would cause sepsis and result in an increased risk for mortality, however two studies proposed that the extent of the disease was not predictive of outcome. [2,4] Three separate studies found significantly higher incidence of the disease in body in the non-survivors.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Although some studies in the literature supported these findings, some others claimed that FGSI scores were not different between survivors and non-survivors. [7][8][9][10][11] Charlson Comorbidity Index (CCI) has been also used in addition to FGSI to predict the prognosis in FG. [12] However, their reliabilities are not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…In a large retrospective study of 68 patients, Corcoran et al 25 described significant differences between non-survivors and survivors on admission laboratory parameters. Non survivors had high serum creatinine and lactate, and low serum calcium.…”
Section: Figure I: Resultsmentioning
confidence: 99%
“…[1][2][3]16 Mortality rates between 4% and 46% have been reported. [1][2][3]16 Early aggressive serial debridement and intravenous antibiotics, followed by some form of durable wound coverage, is standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]16 Mortality rates between 4% and 46% have been reported. [1][2][3]16 Early aggressive serial debridement and intravenous antibiotics, followed by some form of durable wound coverage, is standard therapy. [1][2][3]14,15,17 Because most patients with Fournier's gangrene are older with comorbidities, comesis may not be a primary consideration in the reconstruction.…”
Section: Discussionmentioning
confidence: 99%